2011
DOI: 10.1007/s10549-011-1609-9
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot and feasibility study: prospective proteomic profiling of mammary epithelial cells from high-risk women provides evidence of activation of pro-survival pathways

Abstract: Normal mammary gland homeostasis requires the coordinated regulation of protein signaling networks. However, we have little prospective information on whether activation of protein signaling occurs in premalignant mammary epithelial cells, as represented by cells with cytological atypia from women who are at high risk for breast cancer. This information is critical for understanding the role of deregulated signaling pathways in the initiation of breast cancer and for developing targeted prevention and/or treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…However, leptin’s oncogenic effects in the breast are likely determined by the local interstitial concentration of the adipokine in the mammary epithelial microenvironment, rather than circulating levels. We therefore quantified breast tissue levels from a panel of adipokines, cytokines, and growth factors in surgical excision specimens from women at high risk for breast cancer [26] (Table 1). We did not detect changes in levels of adiponectin, insulin, MCP1, and IL-8, previously reported to be associated with obesity [9, 27, 28].…”
Section: Resultscontrasting
confidence: 85%
“…However, leptin’s oncogenic effects in the breast are likely determined by the local interstitial concentration of the adipokine in the mammary epithelial microenvironment, rather than circulating levels. We therefore quantified breast tissue levels from a panel of adipokines, cytokines, and growth factors in surgical excision specimens from women at high risk for breast cancer [26] (Table 1). We did not detect changes in levels of adiponectin, insulin, MCP1, and IL-8, previously reported to be associated with obesity [9, 27, 28].…”
Section: Resultscontrasting
confidence: 85%
“…These data support observations in the Pten hyper mice as a reduction in PTEN correlated with an increase in phospho-AKT (S473) and Ki-67 in mammory tumors [3]. Additionally, pilot studies using microdissected epithelial cells from random periareolar fine needle aspiration samples have shown that women at risk for breast cancer, have elevated levels of phosphorylated PTEN (S380), total PTEN and active phospho-AKT (S473) [20]. These studies suggest that E2 regulation of PTEN may be an important mechanism in a number of steroid responsive tissues.…”
Section: Discussionsupporting
confidence: 78%
“…Given the key role that matrix stiffness plays in regulating PI3K/AKT-signaling, these studies also provide evidence for the convergence of mechanosignaling and redox activation in aggressive cancers. Since AKT-network signaling is active in premalignant tissue from women at high-risk for breast cancer prior to the development of an invasive phenotype (Pilie, Ibarra-Drendall et al 2011; Ibarra-Drendall, Troch et al 2012), this opens the possibility that combination therapies which target both cellular metabolism and tissue stiffness may serve to more effectively halt disease progression.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%